Smoking habit of children and adolescents: an overview - Grapatsas, Konstantinos; Tsilogianni, Zoi; Leivaditis, Vasileios; Dimopoulos, Emmanouil; Zarogoulidis, Paul; Karapantzos, Ilias; Tsiouda, Theodora; Barbetakis, Nikolaos; Paliouras, Dimitrios; Chatzinikolaou, Fotios; Trakada, Georgia; Skouras, Vasileios (Annals of Research Hospitals, 2017)
Smoking represents one of the largest public health problems due to its detrimental effects on multiple organs of the human body and its association with a variety of chronic and/or lethal diseases. Most smokers start smoking in their youth when growth has not been yet completed and they are more susceptible to the harmful components of tobacco. Purpose of this review was to present current data about the extent of tobacco use in childhood and adolescence, the situations facilitating smoking initiation at an early age and the available policies aiming to prevent early age smoking and to promote smoking cessation in non-adult individuals. Data were collected from the international PubMed database and through research in Google Scholar. Smoking rates among children and adolescents are alarming. Health care specialists should be aware of the real reasons leading to early age smoking, which are mainly the influence of family and its economic status, social life and internet. However, psychological reasons contribute also to early smoking initiation. Interventions in these fields should be achieved in order to prevent children and adolescents from smoking. For those who unfortunately smoke many smoking cessation programs exist worldwide and can help young people to quit smoking. However their results are often controversial. The significant increase of smoking among children and adolescents should be dealt with well-designed national smoking prevention and cessation programs after analyzing thoroughly the causes of young people smoking initiation. Both of these programs, but mainly the one aiming to the prevention part, should be practiced with the cooperation of all social parts, while school should have a central role.